The national image of China in Prominent Malaysian English Newspapers - Ahmad, Abdul Mua'ti @ Zamri; Waheed, Moniza; Mohd Zawawi, Julia Wirza; Hongyu, Mai (Transnational Press London, 2024)
China's image in the Western mainstream media has been quite negative in the last decades. On the other hand, its image in developing countries have become more dynamic and complicated, despite their reliance on Western news agencies for international news. This study applies Framing Theory to examine China’s image in Prominent Malaysian English newspapers. More specifically, it looks into the news sources, news topics, news actors, and news valence. Research samples are drawn from the official websites of the Star and the New Straits Times (NST). The number of China-related reports was 685 and 390 respectively. By way of quantitative content analysis, results showed that news topics, news actors, and news sources all have an impact on the news valence of China-related stories. Among all these factors, news sources have greatest impact. Additionally, it was found that news stories sourced from Chinese media are most positive, while those from Western media are most negative. Meanwhile, news stories sourced from Malaysia and other Asian media are neutral. In essence, this study shows the importance of news sourcing particularly pertaining to international news. Different choice of international news source will lead to different image presentation of a country.